2022
DOI: 10.29259/sijdeb.v6i3.255-276
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Capital Flight and Its Impact on Economic Growth: The Case of WAEMU countries

Abstract: This paper estimates the magnitude of capital flight and analyzes its impact on economic growth in the West African Economic and Monetary Union countries. Over the period from 1970 to 2019, total real capital flight from these countries is positive and significant with a magnitude that amounts to $31,075.26 million in constant dollars, or 17.40 percent of investment. Six countries have experienced significant real capital flight over the past four decades: Ivory Coast, Guinea Bissau, Mali, Niger, Burkina Faso,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…CF hinders economic growth in SSA. Previous research has established the detrimental relation between CF and growth in the literature (Lawal et al , 2017; Orimolade and Olusola, 2018; Ogbenro, 2019; Badwan and Atta, 2019; Orji et al , 2020; Badwan, 2021; Sodji, 2022). A negative impact from the CF is anticipated in the region given its current level in SSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CF hinders economic growth in SSA. Previous research has established the detrimental relation between CF and growth in the literature (Lawal et al , 2017; Orimolade and Olusola, 2018; Ogbenro, 2019; Badwan and Atta, 2019; Orji et al , 2020; Badwan, 2021; Sodji, 2022). A negative impact from the CF is anticipated in the region given its current level in SSA.…”
Section: Resultsmentioning
confidence: 99%
“…The study used the ARDL bounds test approach and showed that both in the short and long run, CF considerably reduces economic growth. Sodji (2022) investigated the influence of CF on economic growth in the West African Economic and Monetary Union using dynamic fixed-effects estimation. The study found that CF harms economic growth over the long term.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The imbalance of capital inflows and outflows in these economies caused by capital flight leads to insufficient internal capital formation in emerging economies and thereby limits the productive capacity of these economies. A shift of saving away from financing the domestic investment of an economy to abroad results in lower economic growth (Sodji, 2022). Therefore, capital controls can be welfare-improving for emerging economies.…”
Section: Introductionmentioning
confidence: 99%